Persepsi Mahasiswa Vokasi IPB 61 terhadap Penggunaan Streak TikTok dalam Kontinuitas Komunikasi - Hasya Maurilla; Amiruddin Saleh; Harvia Atika Zahira (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This journal examines the perceptions of Vocational School students of IPB University Batch 61 regarding the use of TikTok’s streak feature in maintaining communication continuity. The research employed a qualitative method with a phenomenological approach, and data were collected through in-depth interviews with six informants from various study programs who actively use the TikTok streak feature. The findings indicate that most students perceive the streak feature as a marker of communication frequency rather than a measure of relationship closeness. According to the informants, the streak feature encourages daily interactions, although the quality of communication varies, taking forms such as emojis, videos, or short messages. These communication patterns are carried out as an effort to maintain interaction continuity and therefore tend to be phatic in nature. Several factors were also found to influence the sustainability of streaks, including habitual behavior, reciprocal social pressure, and leisure time. Although the communication established through the feature is often considered merely a formality, it helps students develop communicative routines that maintain social relationships and prevent loss of contact. This study demonstrates that TikTok’s streak feature plays a significant role in shaping communication patterns and interpersonal interactions among university students in the digital era.